Growth and Mortality Rate of Scad (Decapterus macrosoma, Bleeker 1851) landed at Inengo Fish Landing Base, Bone Bolango, Gorontalo - Pasisingi, Nuralim (Universitas Islam Negeri Mataram, 2021)
This study aimed to determine the growth pattern and mortality of Scad (Decapterus macrosoma) landed at Inengo Fish Landing Base. A total of 400 fish samples were obtained from the catches of fishers who landed their catch at the landing base using the layered random sampling method. Sampling was carried out from February to March 2021 by measuring the length and weight of the fish samples. Data were analyzed using Microsoft Excel and the FiSAT II application. The results showed that the growth pattern of D. macrosoma was positive allometric with the asymptotic length (L∞)= 279.54 mm, the coefficient of growth rate (K)= 0.49, and the theoretical age of fish (t0)= -0.18 years. The fishing mortality (F) was 2.44 per year; the natural mortality (M) was 0.43 per year; the exploitation (E) was 0.85.